Physical Properties of Extrudates Based on Corn Grit, Mocaf Flour and Gaplek Flour Using a Twin Screw Extruder with Treatment of Moisture Content and Barrel Temperature - Joko Nugroho Wahyu Karyadi; Arifin Dwi Saputro; Devi Yuni Susanti; Dhyas Tanjung Prabowo Putri; Linggar Setianingrum; Rio Bagus Herlambang; Fahmi Baharudin; Ailsa Saraswati Samodra (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Cassava is a commodity that has not been widely innovated on. Mocaf flour and gaplek flour can be innovated as snacks using extrusion technology. This study examined the effects of varying ratios of mocaf/gaplek flour to corn grits (0% / 10% / 20%), initial moisture content (14 / 16 / 18%), and barrel temperature (120 / 130 /140°C) on the physical properties of the extrudate and to characterize the physical properties of the extrudate using PCA analysis. Physical properties such as expansion ratio, particle density, moisture content, color (L and b*), water absorption index (WAI), water solubility index (WSI), and hardness were analyzed. The extrusion process was performed using a SYSLG-IV twin screw extruder (10 15 kg/hour capacity). The addition of mocaf/gaplek flour increased particle density, moisture content, L, and hardness but decreased the expansion ratio. Initial moisture content had a negative effect on the expansion ratio, WAI, and WSI while having positive effect on particle density, moisture content, and hardness. Increasing barrel temperature decreases the expansion ratio and moisture content but increases WAI and WSI. Extrudate treated with 14% moisture content was found to have better physical properties. Keywords: Corn grit, Extrusion, Gaplek flour, Mocaf flour, Physical properties.